Solution -
[tex]\frac{(x^2+ 6x-7)}{7x^2-46x-21} >0[/tex]
⇒[tex]\frac{x^2+7x-x-7}{7x^2-49x+3x-21} >0[/tex]
⇒[tex]\frac{(x-1)(x+7)}{(x-7)(7x+3)} >0[/tex]
⇒ (x-1)(x+7) > 0 and (x-7)(7x+3) > 0 (In order to make the whole polynomial +ve, both numerator and denominator have to be +ve )
⇒ (x-1)>0 and (x+7)>0 or (x-1)<0 and (x+7)<0
and (either both of the polynomials are +ve or -ve)
(x-7)>0 and (7x+3)>0 or (x-7)<0 and (7x+3)<0
⇒ x > 7 , x < -7 , -3/7 < x < 1
Answer
[tex]x \ \epsilon\ (-\infty , -7) \cup (\frac{-3}{7} , 1) \cup (7 , \infty)[/tex]